2010
DOI: 10.1021/jp911123v
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in Organic Ionic Liquids in Distinct Regions Using Charged and Uncharged Orientational Relaxation Probes

Abstract: The temperature-dependent fluorescence anisotropy decay (orientational relaxation) of perylene and sodium 8-methoxypyrene-1,3,6-sulfonate (MPTS) were measured in a series of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (alkyl ) ethyl, butyl, hexyl, octyl) organic room temperature ionic liquids (RTIL). The two fluorescent probe molecules display markedly different rotational dynamics when analyzed using Stokes-Einstein-Debye theory, demonstrating that they are located in distinct environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
209
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(233 citation statements)
references
References 44 publications
21
209
3
Order By: Relevance
“…It should be noted that the non-hydrodynamic behavior is in contrast to the hydrodynamic behavior displayed by large solutes in RTILs. 63,64…”
Section: Orientational Relaxationmentioning
confidence: 99%
“…It should be noted that the non-hydrodynamic behavior is in contrast to the hydrodynamic behavior displayed by large solutes in RTILs. 63,64…”
Section: Orientational Relaxationmentioning
confidence: 99%
“…Nevertheless, viscosities of the ionic liquids have also been altered by increasing the length of the alkyl chain on one of the ions in quite a few studies. [17][18][19][20][21][22][23][24][25]39 In a majority of instances, it has been observed that the experimentally measured reorientation times did not comply with the trends predicted by the Stokes− Einstein−Debye (SED) hydrodynamic theory. 43,44 In other words, τ r versus η/T plots displayed a significant degree of nonlinearity, and also τ r values at a given η/T, especially for nonpolar and dipolar solutes, are found to be lower in ionic liquids with longer alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this heterogeneous liquid structure, highly selective solvation is possible. (36) The resulting diversity of local environments can have a direct impact on the dynamics of processes where solvation environment is important. The effect of environment has been observed in the context of a photoisomerization.…”
Section: Introductionmentioning
confidence: 99%